Evaluation of an Android-Based Application for Monitoring the Spread of Covid-19 in Real-Time - Yasser Djawad; Ridwansyah Ridwansyah; Suhartono Suhartono; Hendra Jaya (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
The increase in the number of patients infected with the Covid-19 virus from day to day shows a fluctuating number. Meanwhile, the spread of the COVID-19 virus is spreading rapidly in various ways and is difficult to predict. Therefore, mapping the spread of the COVID-19 virus is needed. Currently, the existing deployment maps are offline maps that are updated one or more times a day. It does not show real-time deployment and so rapid prevention is not possible. This study aims to develop a mapping system for the spread of the COVID-19 virus in real-time. For this reason, in this study, an Android-based COVID-19 spread monitoring application was developed in real-time using the Prototype Development Model method. The application is developed with an easy user interface to receive it well. The results of the created application show that users who use this application can connect in real-time with the developed map. Furthermore, the location of users who are exposed to or suspected of being exposed to the COVID-19 virus can be displayed in real-time on the developed map. With the map of the COVID-19 spread, it is hoped that early prevention of the spread of the virus and the introduction of patterns of virus spread can be carried out.